УСВОЈУВАЊЕ НА ГРАМАТИЧКИТЕ КАТЕГОРИИ РОД, БРОЈ И ОПРЕДЕЛЕНОСТ КАЈ ИМЕНКИТЕ ВО МАКЕДОНСКИОТ ЈАЗИК ОД СТРАНА НА СТУДЕНТИТЕ – СЛАВИСТИ - Marija Grkova (Philological Studies, 2019)
The above article deals with grammatical categories in Macedonian nouns in Macedonian as a foreign language (MLD students). This study shows that foreign students have issues with grammatical categories in nouns in the process of acquiring the nouns, and also in the process of learning Macedonian. These issues can cause difficulties in learning certain grammatical phenomena, therefore, we pointed them out, along with their solutions, so MLD students will have an easier way of learning. Our suggestion was different kinds of tasks, and how they affect the students’ different needs. The tasks that involve language activities make demands on the individual’s communicative competence. These kinds of tasks are not supposed to be routine or automatic, but they require the use of strategies in communicating and learning. In our opinion, the tasks should contain one grammatical category if the student is a beginner, and two or more grammatical categories, if the student is an intermediate or proficient user of the language.